Travelling pattern and the preferences / inclination of the Arab tourists towards hotel products and services / Zulkifli Ibrahim - Ibrahim, Zulkifli (2007)
This empirical study investigates the Arab tourists' travelling pattern, preferences and inclination towards hotel products and services. The inclination of the Arab tourists towards hotel attributes such as front office, room, food and beverages and other amenities and services are identified. An adaptation of the triangulation approach through a self completed survey among the Arab tourists at selected hotels and short interviews with Arab embassy attache was used to gather the information for this study. This study has given a significant meaning and further insights on the issue being investigated. The results revealed that the majority of the Arab tourists in Malaysia were among married man with family and spouses visiting for a holiday. In addition, the majority of them are from the oil producing countries in the Middle East region such as Saudi Arabia, Kuwait, United Arab Emirates and Syria. The results also signified that the major activities engaged by the respondents were sightseeing plus other activities such as visiting beaches, theme parks, walking/hiking and shopping.